[Recensão a:] Amélia Aguiar Andrade e João Luís Fontes (ed.), Inquirir Na Idade Média: Espaços, Protagonistas e Poderes (sécs. XII-XIV). Tributo a Luís Krus. Lisboa: IEM-FCSH/NOVA, 2015, 245 pp.. ISBN: 978-989-98749-7-8. - Branco, Maria João Violante (2022)
UID/HIS/00749/2013